Optimization of qPCR for detection and quantification of Beauveria bassiana in soil and insect cocoon samples - SYAIFUL AMRI SARAGIH; WIDIHASTUTY WIDIHASTUTY; AISAR NOVITA; RINI SULISTIANI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Saragih SA, Widihastuty, Novita A, Sulistiani R. 2026. Optimization of qPCR for detection and quantification of Beauveria bassiana in soil and insect cocoon samples. Biodiversitas 27 (2): d270231. https://doi.org/10.13057/biodiv/d270231. The optimization of white muscardine fungus Beauveria bassiana-based biocontrol programs and comprehensive risk assessment remain limited due to the lack of standardized, sensitive, and rapid molecular detection methods capable of accurately measuring B. bassiana density in complex environmental matrices. Traditional culture-based detection methods have limitations, including an inability to detect viable but non-culturable fungal states and lengthy incubation periods. In this study, we developed and validated a quantitative PCR (qPCR) assay to detect and quantify B. bassiana in soil and insect cocoon samples. Soil samples were collected from a natural beech forest, while insect cocoon samples were collected from dead insects of the larch sawfly, Pristiphora erichsonii. The qPCR was performed with a specific primer pair obtained during the specificity test, and the standard curve was used to determine the density of B. bassiana in the mixture of DNA extract from the soil and insect cocoon samples. Using ten concentration levels of both genomic DNA and a standard soil DNA, two standard curves were produced. The results showed that the best primer pair among them was BB1962F (5'-GACGGCGTCGGTGTAACGT-3')/BB2156R (5'-GATGTTGTCTGGCGTCTCC-3'). This primer demonstrated specificity by producing a single melting curve peak. The qPCR revealed a standard curve generated with linear correlation with the log10 of B. bassiana genomic DNA (slope = -3.6193). The qPCR employing B. bassiana soil DNA revealed a linear relationship with log10 of B. bassiana dry weight, with a standard curve using B. bassiana soil DNA (ng/g soil) (slope = -3.3935). Although B. bassiana was not found in all soil samples, it was found in five out of 80 dead cocoon samples. In this study, a specific and quantitative qPCR method for the detection of B. bassiana was successfully developed.